Evaluating the Effectiveness of Special and General Allocation Funds on Capital Spending in Indonesia Regional Economies - Rukmini, Meme; Riningsih, Duwi; Nuansari, Shindy Dwita; Yunanto, Ferdy; So, Mayciella (International Journal of Economics Development Research (IJEDR), 2025)
This study examines the effectiveness of Special Allocation Funds (DAK) and General Allocation Funds (DAU) on Regional Capital Expenditures in Regencies and Cities in Indonesia in 2021. The findings indicate that DAK does not have a significant positive effect on capital expenditures, while DAU has a positive and significant impact. However, simultaneous testing results show that DAK and DAU together significantly influence capital expenditures, as evidenced by an F-value of 72.050 with a significance level of 0.000 (< 0.05). These results suggest that while DAK individually does not directly impact capital expenditures, its combination with DAU plays a crucial role in supporting regional investment and infrastructure development. Therefore, optimizing DAK management is necessary to enhance its flexibility and effectiveness in financing capital expenditures, ensuring a more direct contribution to regional development. Local governments should allocate DAU wisely, not only for routine expenditures but also for long-term investments that drive economic growth. Additionally, improving transparency and accountability in budget management is essential to ensure that allocated funds are utilized effectively and efficiently. Future research is recommended to incorporate other variables, such as Local Revenue (PAD) and Revenue Sharing Funds (DBH), to gain a more comprehensive understanding of the factors influencing regional capital expenditures in subsequent years